Awareness about reproductive health, contraceptive methods, STDs including HIV/AIDS, and HPV vaccine, among adolescent girls in district Faridkot in Punjab - Grover, Seema; Garg, Nishi; Rupali, Rupali; Kaur, Balpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adolescents are more vulnerable than adults to unplanned pregnancies and sexually transmitted diseases including HIV/AIDS. Female adolescents have a higher risk of contracting an STD than their male counterparts. Hence creating awareness in them about reproductive health is the need of the hour. Methods: This was a cross sectional school based Study which was conducted in various schools of Faridkot city of Punjab where 400 Adolescent girls of class 11th and 12th age between 16-19 years, studying in English medium schools in district Faridkot through predesigned multiple choice questionnaires. Results: In our study, most of the girls (67%) were not aware about the meaning of reproductive health. Amongst contraceptive methods, 62.5% knew about condoms. The awareness about STDs was highest about HIV/AIDS (70.75%) and low (less than 20%) for other STDs. They also scored low about symptoms and route of transmission of STD’s. Only 17% of the girls knew about HPV vaccine. Attitude towards sex education was positive. Conclusions: Poor knowledge in girls about Reproductive Health and STDs (other than HIV/AIDS) is of serious concern. Therefore, education about reproductive health should be incorporated in the curriculum which should be given through teaching, interpersonal communication, television, health camps and specialist.